Designing the concept for a mobile health solution to educate female scholars residing in a low-to-middle income socio economic setting in Cape Town about HPV and its vaccine - Oliver, Kedebone (Department of Human Biology, 2023)
Introduction Cervical cancer is the second most common cancer in South African women and fourth most common in women worldwide. Human papillomavirus (HPV) infection is the causative agent of 90% of cervical cancers. It can be prevented, especially in younger, non-sexually active individuals through a 2- or 3-dose vaccination. The vaccines are given free of charge to female grade 4 learners (9-15 year-olds) in South African public schools since 2014. The vaccination programme was promoted through educational pamphlets, posters, publications on the government websites, social media, and broadcasts on national radio and television prior to the start of the campaign. However, the available vaccines do not protect against all types of HPVs, and thus consistent education would be useful to advise young girls about safe lifestyle choices. Young people use mobile devices extensively, and therefore these devices may be an effective way to reach them directly, and to engage with them consistently. The project aimed to design the concept for a mobile health (mHealth) solution to aid in educating young female scholars residing in a low-to- middle-income setting in Cape Town about HPV and its vaccine. Methodology A user-centred approach known as the Information systems research (ISR) design framework was used to design the concept for a mHealth solution. It involved three main steps that were applied in a cyclic manner: namely the cycles of relevance, design and rigour. The relevance cycle involved assessment of the needs and knowledge of the target population (grade 4-7 female scholars of the Ikamva Labantwana Bethu tutoring programme in Crossroads) through a quantitative survey with 43 participants, which was followed by two focus group discussion with 8 participants each. The focus group discussion formed part of the design cycle, where a mock mHealth tool (based on the survey results) was presented to the groups to engage them about their attitudes, preferences, and perceptions towards the proposed solution. The rigour cycle involved combining the survey and focus group discussion data with knowledge from literature, for the conceptual design of the mHealth tool. Results A total of 43 learners completed the survey, and all participants indicated that they were vaccinated for HPV at school; however, none of them were able to answer the HPV knowledge questions. There was a high level of access to mobile technologies, as all the participants reported that they had access to cell phones and laptops (own or borrowed). The learners showed a strong preference for learning about sexual health and HPV from schoolteachers and tutors, with 25 out the 41 participants selecting this option, and 52% preferring an interactive learning style. During the focus group discussions, emphasis was placed on the mHealth application having entertainment features, while still being informative. Conclusions There was sufficient access to mobile technologies and WIFI access, which made an mHealth solution feasible. The fact that the participants had all been vaccinated, but they still didn't know what HPV was, showed that an mHealth tool could be useful. The learners prefer to learn interactively, and from their teachers and tutors, which is an element that can be introduced to the mHealth platform through a chatting function and educational video.